New alginate-based interpenetrating polymer networks for water treatment: A response surface methodology based optimization study - Al-Sakkari, E. G.; Abdeldayem, O. M.; Genina, E. E.; Amin, L.; Bahgat, N. T.; Rene, E. R.; El-Sherbiny, I. M.
Different interpenetrating polymeric networks (IPN)based on sodium alginate, carrageenan and bentonite were developed to remove heavy metals and dyes from contaminated water. Four significant preparation factors; crosslinking time, calcium chloride concentration, alginate to carrageenan mass ratio,and bentonite to carrageenan mass ratio were studied and optimized via full factorial design and response surface methodology to determine the optimum composition with highest adsorption capacity. Different optimal conditions and combinations were found depending on the type of heavy metal or dye to be removed. Low calcium chloride concentration was a common factor in all cases of heavy metals and dyes removal which indicates the negative effect of excessive crosslinking on the removal percentage. The adsorption capacity of methylene blue, Fe3+, Ni2+, and Cr3+ ions is 1271, 1550, 1500 and 1540 mg/g adsorbent, respectively. Reusability tests confirmed that the optimized formulations can be reused five successive times without significant drop in their removal efficiency. Upon utilization of the optimized formulations on real contaminated waters from tannery plant and oasis groundwater, they demonstrated an excellent performance as they removed above 95 percent of the original heavy metals contaminants and 40 percent of the acidic dye content.
Keywords: ALGINATE; FACTORIAL DESIGN; INTERPENETRATING POLYMERIC NETWORKS; OPTIMIZATION; RESPONSE SURFACE METHODOLOGY; WATER TREATMENT